2023
DOI: 10.1155/2023/4481354
|View full text |Cite
|
Sign up to set email alerts
|

PPARG: A Promising Therapeutic Target in Breast Cancer and Regulation by Natural Drugs

Abstract: Breast cancer (BC) is the most common type of cancer among females. Peroxisome proliferator-activated receptor gamma (PPARG) can regulate the production of adipocyte-related genes and has anti-inflammatory and anti-tumor effects. Our aim was to investigate PPARG expression, its possible prognostic value, and its effect on immune cell infiltration in BC, and explore the regulatory effects of natural drugs on PPARG to find new ways to treat BC. Using different bioinformatics tools, we extracted and comprehensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…PPARG also contributes to cell cycle dysregulation, related to chemosensitivity [ 34 , 35 ], and influences drug detoxification processes, affecting chemotherapy efficacy [ 36 , 37 ]. Moreover, PPARG's involvement in the inflammatory response is critical for determining chemosensitivity [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…PPARG also contributes to cell cycle dysregulation, related to chemosensitivity [ 34 , 35 ], and influences drug detoxification processes, affecting chemotherapy efficacy [ 36 , 37 ]. Moreover, PPARG's involvement in the inflammatory response is critical for determining chemosensitivity [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of STATs is mediated by Janus Kinases (JAKs) which are activated by IL-6 or leukemia inhibitory factor (LIF) binding to their receptors [139]. The activation of PPARγ has been shown to inhibit the transcription of STAT5 target genes, signifying a reciprocal negative regulation between PPAR and STAT pathways studied in breast cancer cells [140]. Therefore, PPARγ might inhibit P4 signalization during the secretory phase by trans-repression of STATs which results in the non-receptive endometrium or shift in WOI [137,139,140].…”
Section: Negative Impact Of the Pparγ Pathway On The Endometriummentioning
confidence: 99%
“…The activation of PPARγ has been shown to inhibit the transcription of STAT5 target genes, signifying a reciprocal negative regulation between PPAR and STAT pathways studied in breast cancer cells [140]. Therefore, PPARγ might inhibit P4 signalization during the secretory phase by trans-repression of STATs which results in the non-receptive endometrium or shift in WOI [137,139,140]. Additionally, PPARγ increases the expression of the suppressor of cytokine signaling (SOCS) protein which negatively regulates JAK/STAT signaling [141].…”
Section: Negative Impact Of the Pparγ Pathway On The Endometriummentioning
confidence: 99%
See 1 more Smart Citation
“…The Th1/Th2 ratio of tumor patients changes, which leads to inhibition of anti-tumor immune response, so that cancerous cells can survive and improve the appearance and progress of malignant tumors. Li and other researchers consider that the immune microenvironment has an essential part in the development and growth of BC, 104 closely associated with the PI3K/AKT and PD-1/PD-L1 signal transduction pathway and inhibits the progression of lymphoma. 96 They found that Xihuang pill can serially enhance IFN-γ and IL-2, inhibit IL-4 and IL-10, and modulate Th1/Th2 cell balance, improving the immune microenvironment.…”
Section: Direct Inhibition Of Human Bc Cellsmentioning
confidence: 99%